(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Malnutrition is an international problem. According to the National Family Health Survey (NFHS-5), almost half of children aged 0 to 6 years in India are malnourished. Gujarat is also not exempt from this situation and the situation of tribal children is more serious. The tribal population is an educationally, economically and socially deprived class. The causes of malnutrition shown in various researches are directly related to the diet of the tribal society, their traditional customs, practices, changes in the ecosystem, nutritional status. Age at marriage, dietary habits, education, income and age at first intercourse along with cultural aspects are the main reasons. (Chamber and Medinza 2014, Patil 1989, Mandal 2002, Somani 2014, Alian Chowdhury 2011, Gogai 2015, Patel. 2010, Somani and Pawar, 2020). Taking into account the causes of malnutrition given in the previous research, the present study was conducted by the researchers to get information about the causes of malnutrition from the malnourished children of Dang district of South Gujarat and their mothers